10=67t+8

Rewrite the equation as 67t+8=10.

67t+8=10

Combine 67 and t.

6t7+8=10

Subtract 8 from both sides of the equation.

6t7=10-8

Subtract 8 from 10.

6t7=2

6t7=2

Multiply both sides of the equation by 76.

76⋅6t7=76⋅2

Simplify 76⋅6t7.

Cancel the common factor of 7.

Cancel the common factor.

76⋅6t7=76⋅2

Rewrite the expression.

16⋅(6t)=76⋅2

16⋅(6t)=76⋅2

Cancel the common factor of 6.

Factor 6 out of 6t.

16⋅(6(t))=76⋅2

Cancel the common factor.

16⋅(6t)=76⋅2

Rewrite the expression.

t=76⋅2

t=76⋅2

t=76⋅2

Cancel the common factor of 2.

Factor 2 out of 6.

t=72(3)⋅2

Cancel the common factor.

t=72⋅3⋅2

Rewrite the expression.

t=73

t=73

t=73

The result can be shown in multiple forms.

Exact Form:

t=73

Decimal Form:

t=2.3‾

Mixed Number Form:

t=213

Solve for t 10=6/7t+8